2013
DOI: 10.3109/17453674.2013.871137
|View full text |Cite
|
Sign up to set email alerts
|

Short-segment posterior instrumentation combined with anterior spondylodesis using an autologous rib graft in thoracolumbar burst fractures

Abstract: Background and purposeThere are very few data concerning the outcome after short-segment posterior stabilization and anterior spondylodesis with rib grafts in patients suffering from unstable thoracolumbar burst fractures. We have therefore investigated the clinical and radiographic outcome after posterior bisegmental instrumentation and monosegmental anterior spondylodesis using an autologous rib graft for unstable thoracolumbar burst fractures.Patients and methodsThis was a retrospective analysis of 32 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…As regard PA surgery the present study coincides with Jain et al [17] and Aebli et al [18] in the following; improvement of the neurological deficit with significant difference between pre and postoperative state (p < 0.001 * ), surgical correction of the kyphotic angle from the preoperative to postoperative measure about 25.64˚ ± 3.82˚ and less loss of correction in the present study than the other study (0.07˚) adequate decompression of the spinal canal postoperatively(57.35% ± 5.01%) with significant difference between pre and postoperative spinal canal compromise, operative time was less in our study than others (179.85 ± 6.35 min) ,longer hospital stay (6.28 ± 1.3 day) EBL was less in the present study than others (689.28 ± 102.15 cc), improvement of the VAS and ODI score from pre to the postoperative state with total loss of score (6.21 points) and 40% ± 6.3% respectively with significant difference. But the present study reported no neurological complication like PLIF surgery but reported two cases had superficial wound infection which treated conservatively and improved after 2 weeks, 2 cases had loose screws and 2 cases had cage subsidence but didn't affect kyphotic angle (<10˚).…”
Section: Discussionsupporting
confidence: 92%
“…As regard PA surgery the present study coincides with Jain et al [17] and Aebli et al [18] in the following; improvement of the neurological deficit with significant difference between pre and postoperative state (p < 0.001 * ), surgical correction of the kyphotic angle from the preoperative to postoperative measure about 25.64˚ ± 3.82˚ and less loss of correction in the present study than the other study (0.07˚) adequate decompression of the spinal canal postoperatively(57.35% ± 5.01%) with significant difference between pre and postoperative spinal canal compromise, operative time was less in our study than others (179.85 ± 6.35 min) ,longer hospital stay (6.28 ± 1.3 day) EBL was less in the present study than others (689.28 ± 102.15 cc), improvement of the VAS and ODI score from pre to the postoperative state with total loss of score (6.21 points) and 40% ± 6.3% respectively with significant difference. But the present study reported no neurological complication like PLIF surgery but reported two cases had superficial wound infection which treated conservatively and improved after 2 weeks, 2 cases had loose screws and 2 cases had cage subsidence but didn't affect kyphotic angle (<10˚).…”
Section: Discussionsupporting
confidence: 92%
“…The anterior approaches in patients with vertebral fractures requires fixation of only one level rostral and caudal to the fractured vertebral body, whereas in the posterior approach instrumentation may span five or more levels with the the anterion column disrupted with secondary deformity [ 17 18 ]. The anterior approach facilitates complete removal of the injured vertebral disc, which may prevent chronic post-traumatic back pressure [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…To optimize fusion, bone grafts are better maintained under compression. This is achieved more effectively using an anterior approach and plating with bicortical screws [ 17 18 ]. There is little evidence in the literature concerning the efficacy of outcome using the cylinderical mesh titanium cage for postcorpectomy reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations